Influence of rotational vibrations on heat and mass transfer during vertical bridgman growth F germanium crystals - Lyubimova, Tatyana Petrovna; Parshakova, Yanina Nikolaevna (Computational Continuum Mechanics, 2008)
The effect of high-frequency vibrations with small amplitude on the directional solidification of binary alloys is studied numerically. The calculations are made in the framework of a quasi-static approach for gallium doped germanium. The finite volume method is used. It is shown that in terrestrial conditions the influence of rotational vibrations on the radial dopant segregation is rather weak: quite high intensity of vibrations is needed to achieve a significant decrease in the dopant segregation. Under reduced gravity conditions, the effect of vibrations is considerable: the radial dopant segregation becomes uniform even at low-intensity vibrations.